Ecotoxicology of nano-TiO 2-an evaluation of its toxicity to organisms of aquatic ecosystems - Clemente, Z.; Castro, V. L.; Jonsson, C. M.; Fraceto, L. F. [UNESP] (My University, 2012)
The production and use of synthetic nanoparticles is growing rapidly, and therefore the presence of these materials in the environment seems inevitable. Titanium dioxide (TiO 2) presents various possible uses in industry, cosmetics, and even in the treatment of contaminated environments. Studies about the potential ecotoxicological risks of TiO 2 nanoparticles (nano-TiO 2) have been published but their results are still inconclusive. It should be noted that the properties of the diverse nano-TiO 2 must be considered in order to establish experimental models to study their toxicity to environmentally relevant species. Moreover, the lack of descriptions and characterization of nanoparticles, as well as differences in the experimental conditions employed, have been a compromising factor in the comparison of results obtained in various studies. Therefore, the purpose of this paper is to make a simple review of the principal properties of TiO 2, especially in nanoparticulate form, which should be considered in aquatic toxicology studies, and a compilation of the works that have been published on the subject.
Keywords: Aquatic organisms; Ecotoxicology; Nano-tio 2; Nanotechnology; Water